(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Objectives: The objectives of this study were to determine the frequency and to assess the factors leading to Recurrent Laryngeal Nerve (RLN) injury during thyroid surgery at a tertiary care hospital. Study Design: Descriptive case series. Setting: Surgical Unit-I, Fatima Jinnah Medical College/Sir Ganga Ram Hospital, Lahore. Subject and Methods: Four hundreds and seventy patients were included in this study. Patients with pre-existing RLN injury and those with concomitant parathyroid pathology were excluded from the study. RLN injury was documented by post-operative finding of absent vocal cord movement on direct laryngoscopy by the anesthetist at the time of extubation. Results: The mean age of the patients was 45.33±10.20 years and 71.9% were female. Total thyroidectomy was the most common (43%) surgical procedure performed. Fifty nine (12.6%) patients underwent redo surgery and in 61 (13%) patients histopathology report revealed malignant lesion. RLN injury was noted in 18 (3.8%) cases of the total surgeries. The occurrence of RLN injury was significantly higher among Total Thyroidectomy patients (7.4%, p=.006) and those with malignant thyroid lesion (13.1% vs. 2.4%, p=.000). However, there was only insignificant difference between redo and primary surgery (3.9% vs. 3.4%; p=.851). Conclusion: RLN injury is a frequent complication of thyroid surgery and the occurrence is even higher among patients undergoing total thyroidectomy, redo surgery and those with malignant thyroid lesion.